DESIGN AND IMPLEMENTATION OF E-LKPD USING THE LOK-R MODEL FOR ELECTROMAGNETIC WAVE MATERIAL IN SENIOR HIGH SCHOOL - Latifah, Sri; Wiliyanti, Vandan; Sari, Intan Permata (Science Education, Institut Agama Islam Negeri Ponorogo, 2024)
This research project analyses the creation of an E-LKPD utilising the LOK-R model, based on the principles of scientific literacy, specifically tailored for physics education. This research is intended to: (1) Get to know the development process, (2) Analyze the feasibility, and (3) Determine whether this physics learning material using LOK-R based on science literacy about Electromagnetic Waves is interesting and attractive, and has been integrated with the independent curriculum. The method used is a 4D development method (Define, Design, Development, and Dissemination) created by Thiagarajan, this research methodology. The limitation of this research is only in the development stage. For media experts and material experts, ways to get feasibility test devices and to measure interest from teachers and twelfth-grade students at 3 schools in total. This research was carried out at State High School 01 Bandar Lampung, Private High School Perintis 2 Bandar Lampung, and State High School 10 Bandar Lampung, and here are the research results: E-LKPD Physics Material Using the LOK-R Model Based on Science Literacy on Electromagnetic Waves integrated with the independent curriculum is very suitable and interesting as well as ready to be material for distance learning and can train students to learn independently.